Os impasses amorosos na crônica de Paulo Mendes Campos - Oliveira, Edna Caroline Alexandria da Cunha (2018)
This is dissertation to propose a lection of the chronic by Paulo Mendes Campos, about human desert to describe the love problems between man and woman into contexts to refer cultural transmutation time, between age 1950 a 1960, particularly. The texts reference the poetic attribute into hybrid forms as essay, maxim and poetic prose. So, the poet who writes in a lyrical style to contrast poetic himself and to describe the action from love to no love. The discussion to set up between the chronic of the book O amor acaba: crônicas líricas e existenciais and the book Poemas, by Campos. About to build the love relation in the contexts, we investigate the poetic and infidel writing by Campos from to know the influence the news subjects into contexts, by subject displacement and identities decentralize, by Hall. About the love concepts different, we emphasize the theories by Zygmunt Bauman and the pictures putting by Roland Barthes on the book about to love dictionary. In the phase one, we describe the hybrid chronic between journalism and literature to show the double style by Campos. So, we describe style himself from to problematize yours chronic about human desert and to go different ways to love between lovers. In the phase two, we contextual the characteristics from chronic by Campos to describe the affective break between lovers, simultaneously we describe the book O amor acaba. In the phase three, we make intertextual analysis by Brazilian Literature, because, we know the texts are incompletes, so, talking with other texts by traditional literary we extend the concepts to read the love problems by Campos, so, to indicate the literary style for him.